Fabrication Rutile-Phased TiO2 Film with Different Concentration of Hydrochloric Acid Towards the Performance of Dye-Sensitized Solar Cell - Norazlina, A.; Mohamad, F.; Talib, A.; Ahmad, M. K.; Nafarizal, N.; Soon, C. F.; Suriani, A. B.; Mamat, M. H.; Murakami, K.; Shimomura, M. (International Journal of Integrated Engineering, 2020)
In this study, one-step hydrothermal method is demonstrated to synthesis TiO2 double-layer structure by modifying the concentration of hydrochloric acid (HCl). The X-ray diffraction (XRD) pattern analysis suggested that the dominant peak is rutile phase. Interesting morphologies such as cauliflower, chrysanthemum flower or dandelion structures over the nanorods layer were revealed by FE-SEM images and showed substantial effects to the thin film performance. UV-vis absorption spectra of prepared TiO2 film is in UV limitation with band gap energy (Eg) range from 2.57eV to 3.0eV. The optimum photoelectric conversion efficiency of DSSC is 42.5% that exhibited the efficiency of 6.41% for the sample synthesized using equal proportion of de-ionized water and HCl amount or in another word in accordance of ratio 1:1. These results serve as a guidance principle for preparing high quality DSSC thin film.